¡Los muros gritan! El diálogo entre la cultura material y la memoria a través de los carteles de la colección Thommen-Strasser del MKB sobre los movimientos de resistencia en Latinoamérica - Hernanz García, Natalia (Notas de Antropología de las Américas, 2025)
Posters are by nature social objects that inhabit the walls of cities. Depending on the content and the message they convey, posters can be organized as commercial, political, cultural or socially problematic. This text deals with the reflections that, in relation to the poster as an element of material culture, source of knowledge and creator of memory, arose during the process of inventorying a collection of 327 posters from Latin America, with a mostly social theme, which was held at the Museum of Cultures in Basel in 2019.